A novel fibrinogen variant--Praha I: hypofibrinogenemia associated with gamma Gly351Ser substitution - Kotlín, Roman; Chytilová, Martina; Suttnar, Jirí; Salaj, Peter; Riedel, Tomás; Santrůcek, Jirí; Klener, Pavel; Dyr, Jan Evangelista (European journal of haematology, 2007)
OBJECTIVES: A 25-yr-old man from Prague had abnormal bleeding after several surgical operations with low fibrinogen level and hypofibrinogenemia was suspected. PATIENTS AND METHODS: The patient, 25 yr-old male had a low fibrinogen concentration as determined by the thrombin time and immunoturbidimetrical method. His 48-yr-old mother presented with normal coagulation tests, normal fibrinogen level and reported no history of bleeding. To identify the genetic mutation responsible for this hypofibrinogen, genomic DNA extracted from the blood was analyzed. Fibrin polymerization measurement, kinetics of fibrinopeptide release, fibrinogen clottability measurement, mass spectroscopy, and scanning electron microscopy were performed. RESULTS: DNA sequencing showed heterogeneous fibrinogen gammaG351S mutation in the propositus. The mutant chain was found not to be expressed to the circulation by matrix-assisted laser desorption/ionization time of flight mass spectrometry. Scanning electron micrographs of the patient's fibrin clot as well as kinetics of fibrinopeptide release and fibrin polymerization were found to be normal. CONCLUSION: A case of hypofibrinogenemia gammaG351S was found by routine coagulation testing and was genetically identified.
Keywords: krev; Humans; lidé středního věku; serin; Molecular Sequence Data; molekulární sekvence - údaje; Female; dospělí; Microscopy, Electron, Scanning; Glycine; glycin; lidé; fibrinogen; Amino Acid Sequence; Adult; ženské pohlaví; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Male; Middle Aged; mikroskopie elektronová rastrovací; Blood; Fibrinogen; mužské pohlaví; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Serine; sekvence aminokyselin